Energy Storage Materials from Nature through Nanotechnology: A Sustainable Route from Reed Plants to a Silicon Anode for Lithium‐Ion Batteries1. Issue 33 (26th June 2015) - Liu, Jun; Kopold, Peter; van Aken, Peter A.; Maier, Joachim; Yu, Yan
Abstract Silicon is an attractive anode material in energy storage devices, as it has a ten times higher theoretical capacity than its state‐of‐art carbonaceous counterpart. However, the common process to synthesize silicon nanostructured electrodes is complex, costly, and energy‐intensive. Three‐dimensional (3D) porous silicon‐based anode materials have been fabricated from natural reed leaves by calcination and magnesiothermic reduction. This sustainable and highly abundant silica source allows for facile production of 3D porous silicon with very good electrochemical performance. The obtained silicon anode retains the 3D hierarchical architecture of the reed leaf. Impurity leaching and gas release during the fabrication process leads to an interconnected porosity and the reductive treatment to an inside carbon coating. Such anodes show a remarkable Li‐ion storage performance: even after 4000 cycles and at a rate of 10 C, a specific capacity of 420 mA h g−1 is achieved.